2019
DOI: 10.1556/2006.8.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Exercise addiction and its related factors in amateur runners

Abstract: Background and aims This study examines exercise addiction (EA) in amateur runners from a multidimensional approach, including demographics (age, sex, educational attainment, and financial situation), training factors (duration of running activity, weekly time spent running, mean workout distance per session, other sports activities, and childhood physical activity), psychological features (perceived health, life satisfaction, loneliness, stress, anxiety, depression, body shape, and eating disorders)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 32 publications
8
35
0
2
Order By: Relevance
“…Several studies have proposed that criteria for EA be adapted from those used to diagnose substance use disorders per the DSM, including measures of tolerance, withdrawal, and decreased involvement in other activities (for review see Freimuth et al, 2011). Independent of diagnostic criteria, studies have identified behavioral traits associated with EA, such as obsessive-compulsive behavior, loneliness and anxiety (Macfarlane et al, 2016; Lukács et al, 2019). Several other disorders, including substance use disorders, eating disorder, and other behavior addictions such as shopping and sex addiction have been found to co-occur with EA (for review see Freimuth et al, 2011).…”
Section: Additional Models Of Behavioral Addictionsmentioning
confidence: 99%
“…Several studies have proposed that criteria for EA be adapted from those used to diagnose substance use disorders per the DSM, including measures of tolerance, withdrawal, and decreased involvement in other activities (for review see Freimuth et al, 2011). Independent of diagnostic criteria, studies have identified behavioral traits associated with EA, such as obsessive-compulsive behavior, loneliness and anxiety (Macfarlane et al, 2016; Lukács et al, 2019). Several other disorders, including substance use disorders, eating disorder, and other behavior addictions such as shopping and sex addiction have been found to co-occur with EA (for review see Freimuth et al, 2011).…”
Section: Additional Models Of Behavioral Addictionsmentioning
confidence: 99%
“…Nineteen studies only included runners [30,31,34,35,39,44,48,49,51,55,58,[65][66][67]70,[74][75][76] and compared different levels and types of running. Some studies found a positive association with higher self-identity runners and low levels of depression and high self-efficacy [30,[65][66][67]74].…”
Section: Runners Onlymentioning
confidence: 99%
“…There were conflicting results from papers investigating negative addiction; one indicated that with more years spent running came a greater risk of negative addiction [34], while another found no relationship between years of running and addiction [58] and another found a sex difference in that commitment to running can occur without addiction in female runners but not in males [49]. Another paper found that five variables significantly predicted risk of exercise addiction in runners: weekly time spent running, childhood PA, lower educational attainment, anxiety and loneliness [75]. The remaining four cross-sectional studies of runners only found that, since participating in running, they had better emotional well-being, relief of tension, self-image and self-confidence, mood, depression, aggression and anger, anxiety and happiness, but not all reported significance or effect size [31,35,44,48,51].…”
Section: Runners Onlymentioning
confidence: 99%
“…Prevalence for EXD is 0.5-3.5% in the general population [22] and up to > 50% within triathletes [23]. Some research groups also describe pathological excessive exercise as 'exercise addiction' [24][25][26][27][28][29][30][31][32]. Prevalence for exercise addiction is 0.3-42% in various samples [25,30].…”
Section: Exercise Dependence In Athletesmentioning
confidence: 99%